Помогите решить пожалуйста 1. Упростить выражение:
а) (2c + 5d) – (c + 4d);
б) (3a – 4b) – (2a – 3b);
в 7x + 8y) – (5x – 2y);
г) (5c – 6b) – (3c – 5b);
д) a(2b + 1) – b(2a – 1)
2. Решить уравнение:
a) 2(x – 1) = 3(2x – 1)
b) 3 – 5(x – 1) = x – 2
c) 3(x – 2) – 2(x – 1) = 17
d) (7x – 9) + (2x – 8) = 1
e) (12x + 5) + (7 – 3x) = 3

2

Ответы и объяснения

2014-03-26T19:08:19+04:00
А) (2c + 5d) – (c + 4d)=2с+5д-с-4д=с+д
б) (3a – 4b) – (2a – 3b)=3а-4б-2а+3б=а-б
в) (7x + 8y) – (5x – 2y)=7х+8у-5х+2у=2х+10у
г) (5c – 6b) – (3c – 5b)=5с-6б-3с+5б=2с-б
д) a(2b + 1) – b(2a – 1)=2аб+а-2аб+б=а+б
2. Решить уравнение:
a) 2(x – 1) = 3(2x – 1)
2х-2=6х-3
2х-6х=-3+2
-4х=-1
х=1/4
b) 3 – 5(x – 1) = x – 2
3-5х+5=х-2
-5х-х=-2-5-3
-6х=-6
х=1
c) 3(x – 2) – 2(x – 1) = 17
3х-6-2х+2=17
х=17+6-2
х=21
d) (7x – 9) + (2x – 8) = 1
7х-9+2х-8=1
5х=1+8+9
5х=18
х=18/5
e) (12x + 5) + (7 – 3x) = 3
12х+5+7-3х=3
9х=3-5-7
9х=-9
х=-1
  • Участник Знаний
2014-03-26T19:15:18+04:00
A) c - d
б) а - b
в) 2х + 10у
г) 2с - b
д) 2ab + a - 2ab +b = a+b
_______________________

a) 2x - 2 = 6x - 3
-4x = -1
X = 1/4 = 0,25

b) 3 - 5x + 5 = x - 2
-6x = -10
X = 0,6

c) 3x - 6 - 2x + 2 = 17
x= 21

d) 9x =18
x = 2

e) 9x = -9
x = -1